Clinical Characteristics of Peripheral Neuropathy in Eosinophilic Granulomatosis with Polyangiitis: A Retrospective Single-Center Study in China. (4th July 2020) - Zhang, Zhaocui; Liu, Suying; Guo, Ling; Wang, Li; Wu, Qingjun; Zheng, Wenjie; Hou, Yong; Tian, Xinping; Zeng, Xiaofeng; Zhang, Fengchun
Abstract : Objective. To investigate clinical features, independent associated factors, treatment, and outcome of patients with peripheral neuropathy (PN) in eosinophilic granulomatosis with polyangiitis (EGPA). Methods. We retrospectively analyzed clinical data of 110 EGPA patients from 2007 to 2019 in Peking Union Medical College Hospital. The independent factors associated with PN in EGPA were analyzed with univariate and multivariate logistic regressions. Results. In EGPA with PN, paresthesia and muscle weakness were observed in 82% and 33% of patients, respectively. Both the upper and lower limbs were involved in 51% of patients. 30% of EGPA patients had symmetrical multiple peripheral neuropathy, whereas only 16.4% presented with mononeuritis multiplex. Compared to patients without PN, patients with PN had a higher erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor, Birmingham vasculitis activity score (BVAS), and positivity of myeloperoxidase-antineutrophil cytoplasmic antibodies (MPO-ANCA). Regarding manifestations, patients with PN tended to develop weight loss and arthritis or joint pain. Notably, ANCA positivity, arthritis or joint pain, and higher BVAS were found to be independent associated factors for PN in EGPA. Patients with PN more frequently need glucocorticoid pulses and intravenous infusion of cyclophosphamide. With the longest follow-up of 11.0 years, we found that age and cardiac involvement were risk factors for survival, and female was the protective factor. Conclusion. PN in EGPA frequently displays with symmetrical multiple peripheral neuropathy in China. Positive ANCA, arthritis or joint pain, and higher BVAS are the independent associated factors of PN in EGPA. Glucocorticoids with immunosuppressants are vital therapeutic strategy.